Pemberdayaan Lingkungan Dalam Pencegahan Obesitas Pada Remaja Di Masa Pandemi Covid 19 - Nourmayansa Vidya Anggraini; Serri Hutahaean; Teguh Firmansyah; Muchamad Rifki Nuryanta; Vionita Apriliana; Bonieta Dwi Lestari; Muhammad Harits Saifulloh; Nita Junita (IKRA-ITH ABDIMAS, 2023)
Obesity is one of the major chronic health problems, both in developed and developing countries suchas Indonesia. Lifestyles that change rapidly, including diet and activity, cause an increase in the prevalenceof obesity in children aged 5-19 years, which occurs in developing countries. This condition indicates that theproblem of obesity in adolescents requires resolution of the individual adolescents themselves as well as therole of the surrounding environment as part of health management, namely from teachers, parents and peers.This activity aims to provide health education and training to parents, teachers, and adolescent peers relatedto preventing obesity that occurs in adolescents. This activity resulted in an increase in the knowledge ofparents, teachers, and peers from before and after health education and training. It is recommended thatschools continue to carry out health education related to obesity in collaboration with puskesmas and thehealth office.